LATERAL SEISMIC RESPONSE OF MULTISTORY RCC BUILDING FRAME CONSIDERING STATIC SSI EFFECT - Ms Akshaya Ghalimath; Ms. Chaitrali Jamadar; Mr. Mantesh Hatti; Ms.Sheetal More (International Journal of Innovations in Engineering Research and Technology, 2021)
Soil–Structure Interaction is an important issue in the dynamics of structures, being not taken into consideration, in many cases, due to complex volume of computations. The interaction between soil and foundation becomes meaningful especially in the case of rigid structures and foundations. Soil-structure interaction (SSI) analysis evaluates the collective response and dynamic interplay of three linked systems: the structure, the foundation, and the soil underlying and surrounding the foundation. For the analysis of a building frame, the columns at the foundation level are considered as fixed, but in real condition it is not the case. While considering soil in the analysis of building frame 100% fixity may not be ensured Because of the settlement and rotation of foundation, shear force and bending moment in superstructure get altered. This effect is called as “Soil Structure Interaction”.This paper studies the effect of soil-structure interaction on the seismic performance of structures taking into account the prevailing uncertainties. The Motivation for this study stems from the significant uncertainty in the earthquake ground motion and in the properties of the soil and the linear behavior of the structure. There two methods for the computation of the flexible base modeling. The first approach is the so-called Direct Approachand second approach is the Sub-Structure Approach.